Pengaruh Citra Merek dan Pencarian Variasi Terhadap Niat Beli Ulang: Peran Mediasi Kepuasan Pelanggan: Kasus pada Konsumen Lipstik wardah - Reinaldo Dede Putra; Muhammad Irfani Hendri; Harry Setiawan; Nur Afifah; Ahmadi Ahmadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to determine the effect of Brand Image and Variety Seeking on Repurchase Intention among Wardah lipstick customers in Indonesia, with Customer Satisfaction as a mediator. This study used a quantitative approach with a causal associative approach. The population of this study was Indonesian women who have used Wardah lipstick. The sample size was 225 people, using a non-probability sampling technique with a purposive sampling method and processed using SEM-PLS 4.0. Theoretically, this study contributes to enriching the literature and simultaneously provides practical benefits as a reference for Indonesian cosmetics manufacturers in formulating strategies to increase repurchase intention by optimizing customer satisfaction. The results indicate that Brand Image has a significant positive effect on customer satisfaction and Repurchase Intention. Variety Seeking has a significant negative effect on Customer Satisfaction and Repurchase Intention. Customer Satisfaction has a significant positive effect on Repurchase Intention. Furthermore, Customer Satisfaction significantly mediates the influence of Brand Image and Variety Seeking on Repurchase Intention. These findings emphasize the importance of creating sustainable customer satisfaction to foster repurchase intention.